1980
DOI: 10.1039/c39800000848
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum

Abstract: On p. 354, 1. 7 (main text), 4.18 should read 3-76.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Rodrigo and coworkers have observed that diester monoreduction may be used in I-arylnaphthalide lignan synthesis. 49 Reductions in THF may be catalyzed by sodium borohydride (5 mol %).50 Various borane derivatives have been employed in ester reduction. BH3·NHPh2 has been used to reduce aliphatic esters, although aromatic esters are not readily reduced.…”
Section: Reductions Using Metal Hydride Reagentsmentioning
confidence: 99%
“…Rodrigo and coworkers have observed that diester monoreduction may be used in I-arylnaphthalide lignan synthesis. 49 Reductions in THF may be catalyzed by sodium borohydride (5 mol %).50 Various borane derivatives have been employed in ester reduction. BH3·NHPh2 has been used to reduce aliphatic esters, although aromatic esters are not readily reduced.…”
Section: Reductions Using Metal Hydride Reagentsmentioning
confidence: 99%
“…3 0 6 & 2 880, 2 840, 1 740 (GO), 1 595, 1 510, 1490,1465,1435,1330,1230,1200,1170,1130,1040,1005, and 940 cm-'; m/z (%) 458 (M', 70), 399 (9), 339 (loo), 283 (15).…”
Section: (M' 5) 2830970 (C17h1504 100) (Cighlgo7smentioning
confidence: 99%
“…The double Stobbe condensation of a succinic diester with an aromatic aldehyde is a useful synthetic route for the construction of the basic lignan skeleton. [1][2][3][4][5][6][7] Two successive Stobbe condensation reactions of a succinate diester with an aromatic aldehyde generates an (E,E)-dibenzylidenesuccinate (Scheme 1) that is found in naturally occurring lignans such as phebalarin, 8 jatrodien, 9 and taiwanin. 10…”
mentioning
confidence: 99%